Penerapan Pendekatan Pembelajaran Deep Learning dalam Pemahaman Perintah Beriman kepada Kitab-Kitab Allah SWT pada Pembelajaran Pendidikan Agama Islam - Rodhatul Jennah; Agisna Fadilawati; Mazrur (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to describe the application of the Deep Learning approach to improving fifth-grade students' understanding of the command to believe in the holy books of Allah SWT, as stated in Chapter 2 of the book "Education of Islamic Religion and Character Education" published by the Ministry of Education and Culture in 2017. The study was conducted at SDN Pandan Sari as part of an effort to strengthen the quality of Islamic Religious Education learning at the elementary school level. The Deep Learning approach was chosen because it emphasizes in-depth understanding, interconnectedness between concepts, and broadening learning experiences, enabling students to think more critically and reflectively. This study used a qualitative descriptive method. The results indicate that the application of Deep Learning through reflection activities, analysis of meaning, linking material to real-life situations, and assignments requiring higher-order thinking skills strengthened students' ability to understand the meaning of Allah's holy books, understand their functions, and emulate their values. This approach also encouraged the growth of a more meaningful attitude of faith, extending beyond memorization. The study concluded that Deep Learning significantly contributed to improving the quality of Islamic Religious Education (IS) at SDN Pandan Sari, particularly on the topic of faith in the holy books of Allah SWT, through a more meaningful, active learning process that is oriented toward the appreciation of values